INQUIRING THE NEO-IMPERIAL IDEOLOGY IN THE ENGLISH DEPARTMENT CURRICULUM: TEACHING FOR READING AGAINST THE GRAIN USING READER-RESPONSE - Dewi Candraningrum Soekirno (TEFLIN Journal, 2006)
The spread of the so-called indispensable language for the immersion of English in the global world has mesmerized its victims in the classrooms through the operation of curriculum, material, and teaching methodology. Since the perspective of the traditional/structuralism school could not provide enough reader involvement, reader-response is one of the alternatives that support teaching against the grain. It provides the students with a more active exploration of the text in relation to their selves. This active engagement is important from the perspective of pedagogy. It enriches studentcentered methodology. The application, however, must be combined with a critical perspective. This process encourages students to identify the position of power in the literary texts. It allows teachers to explore students responses that will obviously become invaluable resources in the teaching-learning process.